2012
DOI: 10.1159/000339579
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Induction and IL-6 Suppression Are Associated with Aggravated Neuronal Damage in a Lipopolysaccharide-Pretreated Kainic Acid-Induced Rat Pup Seizure Model

Abstract: Objectives: Reportedly, hippocampal neuronal degeneration by kainic acid (KA)-induced seizures in rats <14 days old was enhanced by lipopolysaccharide (LPS). This study was to test the hypothesis that cytokines such as interleukin (IL)-1β, IL-6 and tumor necrosis factor-α are associated with aggravated neuronal damage. Materials and Methods: Sixty male Sprague-Dawley, 14-day-old rats were used. Experiments were conducted in saline, LPS + saline, saline + KA and LPS + KA groups. Intraperitoneal LPS injections (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The serum concentration of IL-6 was in parallel with the size of the cerebral infarction area, an independent risk factor of brain damage. The possible mechanisms is the promotion of aggregation and adhesion of inflammatory cells, partial infarction of brain tissue, activation of matrix metalloproteinases, destruction of the blood-brain barrier, stimulation of platelet activity, promotion of fibrinogen production and reduction of cerebral perfusion ( 42 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The serum concentration of IL-6 was in parallel with the size of the cerebral infarction area, an independent risk factor of brain damage. The possible mechanisms is the promotion of aggregation and adhesion of inflammatory cells, partial infarction of brain tissue, activation of matrix metalloproteinases, destruction of the blood-brain barrier, stimulation of platelet activity, promotion of fibrinogen production and reduction of cerebral perfusion ( 42 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IL-1β is important in the neurotoxicity of LPS [71,72] and secondary brain injury caused by neuroinflammation during traumatic brain injury [73] and ischemia [74][75][76]. Although IL-1β and neuroinflammation may act protectively in certain brain injuries [77], for example improving the function of the blood-brain barrier after injury [78,79].…”
Section: Interleukin-1βmentioning
confidence: 99%
“…Due to the varied action of IL-6, its Pb-induced increase in different parts of the brain can have both positive and negative consequences. IL-6 has been shown to exert both a cytoprotective [71,85,86] and destructive pro-inflammatory [87,88] effect in various studies of neuroinflammation induced by LPS. It is likely that in our research model IL-6 regulates excessive neuroinflammation and protects against extensive damage to brain tissue, which requires clarification through further research on the effects of IL-6 on the brain of animals treated with Pb.…”
Section: Il-6mentioning
confidence: 99%
“…Inhibition of CB1 receptors early after SE suppressed the increase in the expression of Il6 in the hippocampus in the chronic period. There are reports that IL-6, while promoting inflammatory response, can have a neuroprotective effect via the JAK/STAT3 and RAS/MAPK pathways [ 35 , 36 , 37 ], and suppression of Il6 expression could aggravate neurodegeneration [ 37 ]. Other studies showed that in epilepsy models, Il6 upregulation could aggravate neuronal damage [ 38 ].…”
Section: Discussionmentioning
confidence: 99%